THE IMPACT OF SELF-MONITORING ON STUDENTS’ CLASSROOM PARTICIPATION: THE CASE STUDY OF STUDENTS OF ENGLISH IN MOHAMED FIRST UNIVERSITY, OUJDA - Abdellah El Boubekri; Moad Benyahia (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2020)
Self-monitoring is an intriguing psychological construct that has been receiving much attention from the part of the researchers in a wide range of disciplines. At its core rests the proposition that individuals have the ability to control their expressive behavior, and that they vary in the extent of doing so. This difference results in different outcomes regarding how people behave in their social interactions. Since its inception in the 1970s, myriad articles were written on self-monitoring, and many studies were conducted to explore its effects on people’s performance in a variety of contexts; this comprises schools, universities and hospitals, for example. The paper aimed to explore the influence of self-monitoring on students’ classroom participation, since no study has ever been conducted in this regard. To attain this aim, 121 of students of English in Mohamed First University in Oujda were selected to participate in this study. The results have shown that self-monitoring indeed affects students’ classroom participation. The difference between students who are high self-monitors and those who are low self-monitors, which is manifested in how they think and behave and on which basis they do so, accounts for their differing performance related to the various aspects of classroom participation.